Notes on an old problem of Hungarian historical vocalism: the sporadic (?) change of Uralic *u > Hungarian a, á - Holopainen, Sampsa (Finnisch-Ugrische Forschungen, 2023)
This article discusses the alleged sound change Proto-Uralic *u > Hungarian a, á. The etymologies manifesting this change that have been presented in earlier etymological literature are critically examined, and it is shown that a significant portion of them are wrong or based on outdated reconstructions. New explanations for many etymologies are presented, and possible causes for the few convincing examples of *u > a are discussed.